Group Exhibition-Unclaimed Luggage, Circulo de Bellas Artes, Madrid, Spain - Antoniou, Klitsa (My University, 2026)
Unclaimed Luggage, Circulo de Bellas Artes, Madrid, Spain. Organized and Curated by Artrageous Group